PENGARUH MODEL KOOPERATIF STRATEGI TPS TERHADAP HASIL BELAJAR PADA MATERI SPLDV DI MTS - ., Agus Trinawati (Jurnal Pembelajaran Prospektif, 2017)
This study aimed at determining the improvement of learning outcomes of the learners after  the use of Cooperative Strategy TPS Model on SPLDV material in class VIII MTs. Negeri Ketapang. The design of this study was descriptive research method with its subject of the students of class VIII B MTs. Negeri Ketapang. The data collection techniques used were measurement techniques with data collection tools: test, observation sheet for students as a class, learners' individual observation sheet and teacher's observation sheet. The type of test used was essay test. The improved learning outcomes of learners was 6.80%. The average percentage of learners’ activity was classically increased by 27.50%. Individual learner’s activity increased at each stage of the TPS Strategy Model. The average thinking stage increases at 70.63%, the average pairing stage increased at 62.50% it also equally performed the sharing stage that increased at 62.50%. The average percentage of individual learner’s activity increased at 62.50% and teachers’ activity increased at 30.77%. So it was concluded that there was an increase in learning outcomes of the learners after being applied the Model of Co-operative TPS Strategy on SPLDV materialin Class VIII MT's, Negeri Ketapang.